1998
DOI: 10.1046/j.1471-4159.1998.70031327.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Sonic Hedgehog, Patched, and Smoothened mRNA in the Adult Rat Brain

Abstract: Abstract:In vertebrates, Sonic Hedgehog (Shh), Desert Hedgehog (Dhh), and Indian Hedgehog (lhh) genes encode a family of morphogen proteins that are implicated in a wide range of signaling activities, particularly during embryonic development. These secreted proteins are proposed to mediate their effects on target cells by interacting with their putative receptor, Patched (Ptc), and with a seven-pass transmembrane protein, Smoothened (Smo). However, the roles that these signaling molecules may play in adult ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 21 publications
4
87
0
Order By: Relevance
“…It specifies the identity of different cell types in the ventral neural tube in early development (Pfaff and Kintner, 1998;Briscoe et al, 1999;Oppenheim et al, 1999). Although Shh is strong in inducing motor neurons from progenitor cells, there have been few reports characterizing its role in matured neurons (Miao et al, 1997;Traiffort et al, 1998Traiffort et al, , 1999Ho and Scott, 2002). This is the first evidence that nerve axotomy induces upregulation of both Shh and Smo.…”
Section: Discussionmentioning
confidence: 83%
“…It specifies the identity of different cell types in the ventral neural tube in early development (Pfaff and Kintner, 1998;Briscoe et al, 1999;Oppenheim et al, 1999). Although Shh is strong in inducing motor neurons from progenitor cells, there have been few reports characterizing its role in matured neurons (Miao et al, 1997;Traiffort et al, 1998Traiffort et al, , 1999Ho and Scott, 2002). This is the first evidence that nerve axotomy induces upregulation of both Shh and Smo.…”
Section: Discussionmentioning
confidence: 83%
“…Before Shh was shown to directly affect the BG population, Traifford et al [157] and Wallace [113] had already observed high expression levels of Ptch and Gli1 in small cells in the PCL, presumably in BGs, suggesting that Shh signaling pathway was active in these cells. Confirmation of a direct action of Shh came shortly later, when Dahmane and Ruiz-I-Altaba [95] first demonstrated the role of this ligand in BG differentiation, but, intriguingly, not in BG progenitor proliferation [95].…”
Section: Shh and Cerebellar Gliamentioning
confidence: 99%
“…However, particularly in the light of evidence that, late in gestation, Shh becomes expressed within the cortex itself (Traiffort et al, 1998;Dahmane et al, 2001), and that this expression is also eliminated in the NsCre:Shh Fl/Fl mutants (Fig. 7A), direct or secondary effects of Shh loss on cortical interneuron migration, differentiation or survival must also be considered.…”
Section: Reductions Of Somatostatin-and Parvalbuminexpressing Internementioning
confidence: 99%